Impacto da rodovia ES-261 sobre tetrápodes (Espírito Santo, Brasil) - Carmo, Tatiane de Mello do (2019)
The number of animals killed by roadkill exceeds hunting occurrences and natural causes such as disease and predation. The number of trampled vertebrates is estimated to reach millions per year, with 90% being small vertebrates. There is a lack of studies on the impacts caused by roads applying methods capable of detecting different taxa. The present study sought to identify the impact of a small stretch of ES-261 road on the fauna, walking it in order to contemplate all classes of vertebrates and evaluate the possible factors that may be associated with roadkill. The sample area was a 10 km stretch of ES-261, in Santa Teresa, ES. The sampling period was from September 2017 to August 2018 and in total were 600 km covered in twelve months. A total of 1,322 vertebrates were run over, distributed in four classes and 102 taxa. The most representative group was Herpetofauna with 76% of the occurrences. Among the mammal species found is the bat Thyroptera wynnea. The registration of the specimen represents the first registration for the municipality. The roadkill rate was 2.20 ind./km and 0.037 ind./km/day. Most of the recorded species consist of common taxa that inhabit the most varied environments. The most commonly recorded animals were Rhinella crucifer (Little cane toad), Didelphis aurita (Black-eared Skunk), Elapomorphus quinquelineatus, Tropidurus cf. torquatus (Calango), Sicalis flaveola (Canary) and Sporophila caerulescens (Coleirinho). Callicebus personatus (Guigó or Sauá) and Leopardus guttulus (Wildcats) are on the Holy Spirit endangered list and on the National list in the Vulnerable (VU) and Saltator similis (Cracked Iron) are present only in the regional list of endangered species as Vulnerable (VU). There was a higher occurrence of roadkill in stretches of straight and runs, and in stretches associated with eucalyptus forests and plantations. Roadkills were also associated with rainfall, temperature and seasonality. The clearing of the highway prior to the commencement of collections showed that the highway clears itself within 24 to 48 hours by actions of butcher animals, vehicle movements, or wind. The monitored stretch does not have mitigation measures of fauna roadkills, making it necessary to install speed reducers, insert and maintain signs and driver awareness through environmental education to reduce the number of animals victims of collisions.